Exploring of antioxidant and antibacterial properties of novel 1, 3, 4-thiadiazole derivatives: Facile synthesis, structural elucidation and DFT approach to antioxidant characteristics. (February 2022) - Muğlu, Halit; Akın, Mustafa; Çavuş, M. Serdar; Yakan, Hasan; Şaki, Neslihan; Güzel, Emre
Abstract: In recent years, compounds containing thiophene and 1, 3, 4-thiadiazole skeletons have become important cyclic compounds, especially in medicinal chemistry. In this manner, we synthesized and isolated seven 1, 3, 4-thiadiazole derivatives with thiophene groups and fully characterized by elemental analysis and general spectroscopic methods such as 1 H NMR, 13 C NMR, and FT-IR. Antibacterial activities of the title compounds were investigated by using TLC-Dot blot, macro dilution, well diffusion, and growth curve analysis methods. Compounds 1 and 6 showed inhibitory activities against all tested gram-negative and gram-positive bacteria. TLC-DPPH and DPPH assays, on the other hand, were performed to detect the antioxidant activities of the 1, 3, 4-thiadiazole derivatives and compound 1 exhibited the highest antioxidant activity at all tested concentrations. QTAIM and NCI calculations were performed as well as structural, electronic, and spectral analyzes using density functional theory (DFT). Calculations were carried out at the B3lyp/6–311 + +g(2d, 2p) level of theory, and the data were used to examine the antioxidant activity of the compounds. Graphical Abstract: ga1 Highlights: A series of novel 1, 3, 4-thiadiazole compounds were synthesized. The structures of all compounds were elucidated using spectroscopic techniques. Antioxidant activities of the compounds were tested. Theoretical calculations were accomplished and compared with experimental results.